Measuring Banking Efficiency by Using Roaa and Roae: Evidence from the European Union - Mihaita-Cosmin Popovici (CES Working Papers, 2014)
In this paper, we want to analyse how efficiency evolves in the European Union 28 over the period 2003 – 2012. This period is selected to highlight the evolution before and after the global financial crisis. We used a sample of over 1000 banks with data available for at least ten years and at least three banks for each country. For measuring bank efficiency, we used two of the most popular financial ratios, Return on Average Assets (ROAA) and Return on Average Equity (ROAE). Our results showed that European Union integration can be improved and further reforms could be implemented and bank are affected differently by the international financial crisis.
Keywords: F15; F36; G21; 330; European Union; ROAA; ROAE; Bank Efficiency